Surgical management of gastrointestinal stromal tumors: a single center experience - Poškus, Eligijus (Termedia Publishing House, 2014)
INTRODUCTION: Gastrointestinal stromal tumors (GISTs) are the most common mesenchymal tumors of the gastrointestinal (GI) tract. Although the therapy targeted at inhibiting tyrosine kinases has shown dramatic results in metastatic and inoperable GISTs, the mainstay of treatment in primary localized forms remains surgical resection. AIM: To provide an overview of our experience of GIST diagnosis and management, with emphasis on comparison of minimally invasive and open surgical resection for primary GISTs. MATERIAL AND METHODS: We retrospectively reviewed the medical records of all patients who underwent surgical removal of GISTs from 2008 to 2012. Patient demographics, clinical data, surgery, complications, histopathological data and clinical course were analyzed. RESULTS: Forty-four patients were identified. Average age at diagnosis was 63 years. Minimally invasive (MIS) and open surgery (OS) were each attempted in 22 (50.0%) patients. Laparoscopic removal was performed in 20, laparoendoscopic in 1, and laparoscopy-assisted endoscopic removal in 1. Conversion to an open procedure was performed in 4 (18.2%). We found significant differences in postoperative length of stay (8.5 days vs. 10.1 days, p < 0.001) and tumor size (2.93 cm vs. 5.78 cm, p = 0.018) between MIS and OS groups, respectively. CONCLUSIONS: Laparoscopic removal is safe and effective for GISTs not exceeding 6 cm. Gastroesophageal junction and cardia GISTs require careful preoperative evaluation and planning to remove safely. We recommend avoiding laparoscopic removal of these tumors due to the high rate of conversion (100.0%) to an open procedure. Laparoendoscopic surgical approach is an appropriate technique for removal of small-sized intraluminal benign GISTs not involving the muscularis propria layer.